HIV-2 capsids distinguish high and low virus load patients in a West African community cohort - Onyango, Clayton O.; Leligdowicz, Aleksandra; Yokoyama, Masaru; Sato, Hironori; Song, Haihan; Nakayama, Emi E.; Shioda, Tatsuo; de Silva, Thushan; Townend, John; Jaye, Assan; Whittle, Hilton; Rowland-Jones, Sarah; et al. (Vaccine, 2010)
HIV-2 causes AIDS similar to HIV-1, however a considerable proportion of HIV-2 infected patients show no disease and have low plasma virus load (VL). An analysis of HIV-2 capsid (p26) variation demonstrated that proline at p26 positions 119, 159 and 178 are more frequent in lower VL subjects while non-proline residues at all three sites are more frequent in subjects with high VL. In vitro replication levels of viruses bearing changes at the three sites suggested that these three residues influence virus replication by altering susceptibility to TRIM5α. These results provide new insights into HIV-2 pathogenesis.